2022
DOI: 10.3389/fpsyg.2022.830698
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Correlation Between Quality of Life and Unhealthy Emotion Among Patients With Endometriosis

Abstract: ObjectiveTo investigate the influence of quality of life (QOL) on unhealthy emotions as well as relevant factors among patients with endometriosis for supporting relevant clinical care.MethodsA convenience sampling method was used to administer questionnaires to 139 patients with endometriosis, using the Hamilton Anxiety Inventory (HAMA), the Depression Anxiety Scale (SDS), and the SF-12 Health Survey Short Form, and the results were analyzed. The SPSS20.0 software was used for statistical analysis on relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Therefore, the objective of this study was to determine if there are differences in the levels of emotional dysregulation in patients with cyclical and non-cyclical CPP. This is one of the few studies carried out in Latin America where specialized endometriosis care centers are very limited 45,29 High levels of depression and anxiety were found in both groups of patients with CPP, which coincided with previous studies [41][42][43][44] , however, the present work is the rst one in demonstrating higher global scores in depression, anxiety as a trait and state, and generalized anxiety in women with non-cyclical CPP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the objective of this study was to determine if there are differences in the levels of emotional dysregulation in patients with cyclical and non-cyclical CPP. This is one of the few studies carried out in Latin America where specialized endometriosis care centers are very limited 45,29 High levels of depression and anxiety were found in both groups of patients with CPP, which coincided with previous studies [41][42][43][44] , however, the present work is the rst one in demonstrating higher global scores in depression, anxiety as a trait and state, and generalized anxiety in women with non-cyclical CPP.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it was observed that most women with cyclical pain had not been married, and most women with non-cyclical pain do not have children. Low social support and family networks must maintain depressive and anxious states [57][58] , so women with endometriosis may be more vulnerable to living with chronic emotional dysregulation, which is associated with low quality of life 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the objective of this study was to determine if there are differences in the levels of emotional dysregulation in patients with cyclical and non-cyclical CPP. This is one of the few studies carried out in Latin America where specialized endometriosis care centers are very limited [ 29 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was observed that most women with cyclical pain had not been married, and most women with non-cyclical pain do not have children. Low social support and family networks must maintain depressive and anxious states [ 59 , 60 ], so women with endometriosis may be more vulnerable to living with chronic emotional dysregulation, which is associated with low quality of life [ 45 ]. Marital status and number of children are not predictors of emotional well-being in midlife in women, but rather the quality of relationships [ 51 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies before the pandemic highlighted that this disease and its complications can have an impact on QoL, affecting physical and psychological health and social and working life [6][7][8][9][10]. The QoL is negatively related to anxiety and depression in women with endometriosis [11]. The relationship between QoC and QoL has often been debated [12].…”
Section: Introductionmentioning
confidence: 99%